If Materialism Is Not the Solution, Then What Was the Problem? - Jackson, Robert (The Nordic Journal of Aesthetics, 2016)
What follows is a cursory response to Graham Harman’s article “Materialism is Not the Solution.” It seeks to branch out his conception of ‘form’ and more specifically, ‘aesthetic form’ whilst expanding on Harman’s principal objections to the materialist account of change, and how this may challenge the contemporary aesthetic trajectory of relational encounter: particularly Bourriaud’s Relational Aesthetics (2002). Quite generally, Harman’s Object Oriented Ontology might be understood through two chief aesthetic mechanisms; the contingency of counterfactuals complimented with the preliminary development of a nonmodern formalism. The latter is briefly cashed out in a philosophical juxtaposition to Greenberg and Fried’s modernist principles.